Graphene Oxide Facilitates Solvent‐Free Synthesis of Well‐Dispersed, Faceted Zeolite Crystals. (4th October 2017) - Li, Hui; Liu, Xing; Qi, Siqi; Xu, Linli; Shi, Guosheng; Ding, Yihong; Yan, Xiaoying; Huang, Yong; Geng, Jianxin
Abstract: Zeolites with molecular dimension pores are widely used in petrochemical and fine‐chemical industries. While traditional solvothermal syntheses suffer from environmental, safety, and efficiency issues, the newly developed solvent‐free synthesis is limited by zeolite crystal aggregation. Herein, we report well‐dispersed and faceted silicalite ZSM‐5 zeolite crystals obtained using a solvent‐free synthesis facilitated by graphene oxide (GO). The selective interactions between the GO sheets and different facets, which are confirmed by molecular dynamics simulations, result in oriented growth of the ZSM‐5 crystals along the c‐axis. More importantly, the incorporation of GO sheets into the ZSM‐5 crystals leads to the formation of mesopores. Consequently, the faceted ZSM‐5 crystals exhibit hierarchical pore structures. This synthetic method is superior to conventional approaches because of the features of the ZSM‐5 zeolite.